2017
DOI: 10.1007/s41130-017-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Stated preferences: a unique database composed of 1657 recent published articles in journals related to agriculture, environment, or health

Abstract: Numerous articles dealing with stated preferences are published every year in journals related to agriculture, environment, or health. Hence, it is not easy to find all the relevant articles when performing a benefit transfer, a meta-analysis, or a review of literature. Also, it is not easy to identify trends or common practices in these fields regarding the elicitation method. We have constructed and made available a unique database comprising 1657 choice experiment and/or contingent valuation articles publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…blocking in experimental design and the type of qualitative methods used in a DCE). Third, our observation of less rapid growth in the number of empirical DCEs (compared to the growth observed in previous reviews) matches the trend in the preference research to focus on the broad range of stated preference methods available (rather than DCEs exclusively) [4, 5, 347].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…blocking in experimental design and the type of qualitative methods used in a DCE). Third, our observation of less rapid growth in the number of empirical DCEs (compared to the growth observed in previous reviews) matches the trend in the preference research to focus on the broad range of stated preference methods available (rather than DCEs exclusively) [4, 5, 347].…”
Section: Discussionsupporting
confidence: 80%
“…3). This less consistent increase might be explained by the presence of many competing stated preference methods [4, 5, 347]. We hypothesise that other methods may be increasing in popularity or becoming more useful in health settings [348].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of variation across studies is typical for valuation studies and an important motivation for meta‐analysis (Rolfe et al , ). In addition, we see that the number of choice experiment studies increased compared to contingent valuation methods studies over our data period (see also Mahieu et al , ). The descriptive analysis also showed that willingness to pay for grassland ES was higher for a reduction in grassland intensity levels in a mountain region and lower for a switch from cropland to grassland in other regions (Figure ).…”
Section: Resultsmentioning
confidence: 54%
“…3 The technique is mainstream in marketing, transport, and environmental economics, where it is used to predict individual and collective choices. 4,5 Its application in healthcare has grown exponentially 6,7 because the method is easy to apply and appears efficient. [8][9][10][11] DCEs in health economics are commonly used for valuing health and nonhealth outcomes, investigating trade-offs between health and nonhealth outcomes, and developing priority setting frameworks.…”
Section: Introductionmentioning
confidence: 99%